Limestone Sea Stacks (Rauks) Record Past Sea Levels and Rocky Coast Evolution in the Baltic Sea (Gotland and Fårö Islands, Sweden) - Strzelecki, Mateusz C.; Duszyński, Filip; Tyszkowski, Sebastian; Zbucki, Łukasz (Frontiers in Earth Science, 2022)
In this article, we explore the potential for sea-level change and rocky coastal evolution reconstruction hidden in one of the most intriguing rocky coastal landforms in the Baltic Sea region—rauks. Those unique limestone sea stacks are preserved along the coasts of a number of Swedish islands, with Gotland and Fårö as primary locations. We contributed to the long-standing debate on their origin and attempted to investigate the modern geomorphological processes operating on rauks using novel approaches in rock coast studies, including Schmidt hammer rock tests (SHRT)—to characterize zonation in the degree of coastal landforms weathering; traversing micro-erosion meters (TMEM)—to calculate shore platform downwearing rates; and terrestrial laser scanning (TLS) to monitor coastal abrasion and detect sea-level markers (notches) and describe their size and shapes. Our study shows the dominance of mesoscale changes in the shore platform morphology (erosion scars, spalling, and block erosion) over the microscale downwearing carried out by abrasion. We argue that the preservation of rauks along the modern coast of Baltic islands is a result of a favorable sequence of events including the rapid land uplift and their lithological resistance, significantly higher than observed on surrounding platforms and cliffs formed in different types of limestone. Our findings prove that the microrelief of rauks in the form of well-preserved notches records the sea-level changes from at least the late Ancylus Lake period. Finally, we incorporate the results of our observations into the classic notions of rauk formation and highlight the effect of cutting off sea stacks from the operation of littoral processes as a consequence of land uplift and dominance of subaerial weathering over the wave action.